Anaesthetic Management for Laparotomy in a patient with Ankylosing Spondylitis - Hasan, Mohammad Rajibul; Sharmin, Tahmina; Islam, Md Shafiqul; Chowdhury, Mamunur Rashid; Islam, Md Zahidul; Sharma, Netay Kumer (Community Based Medical Journal, 2017)
It is a great challenge for an anaesthesiologist to manage a case of severely affected ankylosing spondylitis with limited available facilities as it produces lots of problem associated with it. We report a case where bilateral tranchal vagotomy and gastro-jejunostomy was done for gastric outlet obstruction in a patient of ankylosing spondylitis. This report giving importance of pre-anaesthetic assessment of any anatomical deformity and discussion of anaesthetic complications to be faced, decision of anaesthetic technique as well as proper counseling of patient. CBMJ 2017 July: Vol. 06 No. 02 P: 38-41